Endothelial HMGB1 Is a Critical Regulator of LDL Transcytosis via an SREBP2–SR-BI Axis. Issue 1 (January 2021) - Ghaffari, Siavash; Jang, Erika; Naderinabi, Farnoosh; Sanwal, Rajiv; Khosraviani, Negar; Wang, Changsen; Steinberg, Benjamin E.; Goldenberg, Neil M.; Ikeda, Jiro; Lee, Warren L.
Abstract : Objective: LDL (low-density lipoprotein) transcytosis across the endothelium is performed by the SR-BI (scavenger receptor class B type 1) receptor and contributes to atherosclerosis. HMGB1 (high mobility group box 1) is a structural protein in the nucleus that is released by cells during inflammation; extracellular HMGB1 has been implicated in advanced disease. Whether intracellular HMGB1 regulates LDL transcytosis through its nuclear functions is unknown. Approach and Results: HMGB1 was depleted by siRNA in human coronary artery endothelial cells, and transcytosis of LDL was measured by total internal reflection fluorescence microscopy. Knockdown of HMGB1 attenuated LDL transcytosis without affecting albumin transcytosis. Loss of HMGB1 resulted in reduction in SR-BI levels and depletion of SREBP2 (sterol regulatory element-binding protein 2)—a transcription factor upstream of SR-BI. The effect of HMGB1 depletion on LDL transcytosis required SR-BI and SREBP2. Overexpression of HMGB1 caused an increase in LDL transcytosis that was unaffected by inhibition of extracellular HMGB1 or depletion of RAGE (receptor for advanced glycation endproducts)—a cell surface receptor for HMGB1. The effect of HMGB1 overexpression on LDL transcytosis was prevented by knockdown of SREBP2. Loss of HMGB1 caused a reduction in the half-life of SREBP2; incubation with LDL caused a significant increase in nuclear localization of HMGB1 that was dependent on SR-BI. Animals lacking endothelial HMGB1 exhibited less acute accumulation of LDL in the aorta 30 minutes after injection and when fed a high-fat diet developed fewer fatty streaks and less atherosclerosis. Conclusions: Endothelial HMGB1 regulates LDL transcytosis by prolonging the half-life of SREBP2, enhancing SR-BI expression. Translocation of HMGB1 to the nucleus in response to LDL requires SR-BI. Abstract : Supplemental Digital Content is available in the text.